2020
DOI: 10.1016/j.bpobgyn.2020.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer screening: Current status and future directions

Abstract: Ovarian cancer is the third most common gynaecological malignancy and the most lethal worldwide. Most patients are diagnosed with advanced disease which carries significant mortality. Improvements in treatment have only resulted in modest increases in survival. This has driven efforts to reduce mortality through screening. Multimodal ovarian cancer screening using a longitudinal CA125 algorithm has resulted in diagnosis at an earlier stage, both in average and high risk women in two large UK trials. However, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 86 publications
2
56
0
Order By: Relevance
“…In recent years, features such as age, pathological stage, lymph node metastasis and distant metastasis have been commonly used in clinical work to predict the prognosis of patients with OC (Mittermeyer et al, 2013;Yuan et al, 2017;Zwakman et al, 2017;Hua et al, 2019), but the accuracy of these factors is insufficient. With the development of high-throughput sequencing technology, an increasing number of mRNAs have been discovered as biomarkers that can be used to evaluate and predict the prognosis of OC (Buttarelli et al, 2020;Nash and Menon, 2020;Zhang et al, 2020;Zhou et al, 2020). For instance, some scholars found that the high expression of TET3 was related to the progression of OC and the poor prognosis of patients (Cao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, features such as age, pathological stage, lymph node metastasis and distant metastasis have been commonly used in clinical work to predict the prognosis of patients with OC (Mittermeyer et al, 2013;Yuan et al, 2017;Zwakman et al, 2017;Hua et al, 2019), but the accuracy of these factors is insufficient. With the development of high-throughput sequencing technology, an increasing number of mRNAs have been discovered as biomarkers that can be used to evaluate and predict the prognosis of OC (Buttarelli et al, 2020;Nash and Menon, 2020;Zhang et al, 2020;Zhou et al, 2020). For instance, some scholars found that the high expression of TET3 was related to the progression of OC and the poor prognosis of patients (Cao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of high-throughput sequencing, several patient genome databases have been established, which have enabled us to gain a more systematic and comprehensive understanding of patients' genome changes. By mining databases, we identified a number of biomarkers associated with clinical outcomes (Buttarelli et al, 2020;Nash and Menon, 2020;Zhang et al, 2020;Zhou et al, 2020). However, a single gene cannot accurately predict the outcomes of OC.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the success of cervical and breast cancer screening, as well as the rather modest increase in survival from improved treatment, there have been fervent efforts to boost ovarian cancer survival via screening using CA125, an epitope of MUC16, a large glycoprotein marker. However, the accuracy of this biomarker is still questionable, although more effective screening strategies with CA125 are being developed [4]. As outlined before, therapeutic advances have led to only a small increase in ovarian cancer survival rate over the years.…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual rate of OC patients diagnosed at early stage is as low as 20%, indicating the most OC patients are diagnosed at advanced stages, which largely accounts for the unsatisfactory prognosis of OC patients [1,2]. Obviously, the unfavorable outcomes suggest the defects of the current biomarkers and treatments of OC and it is vital to explore novel diagnostic and prognostic biomarkers, and therapeutic targets to improve the e ciency of diagnosis and treatment in OC.…”
Section: Introductionmentioning
confidence: 99%